Entrepreneurial you : - Clark, Dorie (Harvard Business Review Press, 2017)
What does it take to create the career you want? It's no secret that the world of work has changed, and we're shifting toward an ever more entrepreneurial, self-reliant, work-from-wherever-you-are economy. That can be a liberating force, and many professionals dream of becoming independent, whether by starting their own businesses, becoming consultants or freelancers, or developing a sideline. But there's a major obstacle professionals face when they contemplate taking the leap: how to actually make money doing what they love. You may have incredible talent and novel ideas, but figuring out how to get started, building your reputation in a new realm, developing multiple revenue streams, and bringing in a steady flow of new clients can be a daunting prospect. Dorie Clark, a successful entrepreneur and author, has done it all. And in Entrepreneurial You she provides a blueprint for professional independence, with insights and advice on building your brand, monetizing your expertise, and extending your reach and impact online. In short, engaging chapters, she outlines the necessary elements and concrete tactics for entrepreneurial success. She shares the stories of entrepreneurs of all kinds--from consultants and coaches to podcasters, bloggers, and online marketers--who have generated six- and seven-figure incomes. This book will be your hands-on guide to building a portfolio of revenue streams, both traditional and online, so that you can liberate yourself financially and shape your own career destiny.